SENSITIVITY OF HENNA LEAVE (Lawsonia inermis L.) SOLUTION TOWARD Aeromonas hydrophila - Mazdalifah Lubis; Morina Riauwaty; Iesje Lukistyowati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Research was conducted from Juni to October 2016, at the labory Examination of Fish Disease, Fisheries and Marine Sciences Faculty of Riau University. The Purpose of this study was to determine the sensitivity of henna leave (L. inermis) as antimicrobial to A. hydrophila, the range of Minimal Inhibitory Concentration (MIC) and the lethal dose (LD50) henna leave (L. inermis) solution against to catfish (Pangasius hypopthalmus) (7-9 cm) by immersion. The research method used doses K : Control (Novobiocin); D1: 100% (10000 ppm); D2: 90% (9000 ppm); D3: 80% (8000 ppm); D4: 70% (7000 ppm); D5: 60% (6000 ppm); D6: 50% (5000 ppm); D7: 40% (4000 ppm); D8: 30% (3000 ppm); D9: 20% (2000 ppm) dan D10: 10% (1000 ppm). The result showed that henna leave solution was effectively to inhibit A. hydrophila bacteri at dose 60% (6000 ppm) with clear zone 9.22 mm and number of colonies 111.00 x 108 cfu/mL. LD50 test was obtained in the dose 5727 ppm among 24 hours.Key words: Henna Leave, Aeromonas hydrophila, antimicrobial, LD50